Could hyperlipidemia be a risk factor for corticobasal syndrome? - a pilot study - Madetko-Alster, Natalia; Alster, Piotr; Bartošová, Tereza; Klempíř, Jiří; Migda, Bartosz; Przewodowska, Dominika; Migda, Anna; Friedman, Andrzej (Neurologia i Neurochirurgia Polska, 2023)
INTRODUCTION: Corticobasal syndrome (CBS) is a specific clinical manifestation shared by multiple pathologies. The exact mechanism of this phenomenon remains unclear. Differential diagnosis of CBS in everyday clinical practice is challenging, as this syndrome can overlap with other entities, especially progressive supranuclear palsy Richardson-Steele phenotype (PSP-RS). Several papers have suggested a possible role of vascular pathology as a linking factor in the pathogenesis of CBS based on different neuropathologies. This paper analyses differences in the occurrence of the most common vascular risk factors such as hypertension and lipid profile with respect to dietary habits among patients who fulfill the diagnostic criteria for probable/possible CBS and PSP-RS. MATERIAL AND METHODS: Seventy (70) patients in total were included in the study. Exclusion criteria comprised hydrocephalus, stroke in the past, the presence of marked vascular changes in white matter defined as the presence of vascular change ≥ 1 mm in 3T MRI, medical history of hyperlipidemia or the use of drugs that could impact upon lipid metabolism before the initiation of the neurodegenerative disease, and neoplastic focuses in the central nervous system. Patients with diabetes, or with BMI exceeding 18-25, or who were smokers, or who were affected by chronic stress were also excluded. Data was analysed statistically using the Shapiro-Wilk test, the U Mann-Whitney test for group comparison, and a Bonferroni correction to control the false discovery rate (FDR). RESULTS: Our obtained results indicated a statistically significantly higher level of total cholesterol in the CBS group (p = 0.0039) without a correlation with dietary habits. CONCLUSIONS AND CLINICAL IMPLICATIONS: The results obtained in our study may suggest a possible role of vascular pathology in CBS development. This issue requires further research.
Keywords: Pilot Projects; hyperlipidemie; Risk Factors; neurodegenerativní nemoci; Humans; lidé; progresivní supranukleární obrna; Hyperlipidemias; Corticobasal Degeneration; Neurodegenerative Diseases; Supranuclear Palsy, Progressive; pilotní projekty; rizikové faktory; kortikobazální degenerace